1994
DOI: 10.1212/wnl.44.7.1203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intravenous penicillin G and oral doxycycline for treatment of Lyme neuroborreliosis

Abstract: To compare the efficacy of oral doxycycline and IV penicillin G for the treatment of neuroborreliosis, we randomized consecutive patients with Lyme neuroborreliosis to receive either IV penicillin G (3 g q 6 h) or oral deoxycycline (200 mg q 24 h) for 14 days. All patients had antibodies against Borrelia burgdorferi in serum, CSF, or both, or had a positive CSF culture. Twenty-three patients randomized to penicillin G and 31 patients to doxycycline were included in the study. All patients improved during treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(83 citation statements)
references
References 1 publication
3
76
0
4
Order By: Relevance
“…Which antimicrobial agents have been shown to be effective or ineffective in the treatment of nervous system Lyme disease Four studies were Class II (three in adults with neuroborreliosis, 15,18,19 one in children 48 ). All were rated Class II with regard to at least one of their predetermined objective measures of disease activity: ELISA, CSF cell count or culture, all of which were apparently measured in masked fashion.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Which antimicrobial agents have been shown to be effective or ineffective in the treatment of nervous system Lyme disease Four studies were Class II (three in adults with neuroborreliosis, 15,18,19 one in children 48 ). All were rated Class II with regard to at least one of their predetermined objective measures of disease activity: ELISA, CSF cell count or culture, all of which were apparently measured in masked fashion.…”
mentioning
confidence: 99%
“…18 In each study, both regimens demonstrated comparable rates of efficacy. [19][20][21][22] Although most studies have focused on patients with Lyme meningoradiculitis, two have assessed treatment response in patients with Lyme encephalopathy, defined as objectively demonstrable cognitive abnormalities on formal mental status testing or neuropsychological testing. In the first 23 (Class III), 27 adults with Lyme encephalopathy, polyneuropathy, or both were treated with ceftriaxone, 2 g IV daily for 2 weeks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…treatment of neurological disease since clinical trials found that doxycycline was not inferior to intravenous penicillin for neuroborreliosis. 8 …”
Section: Diagnosismentioning
confidence: 99%
“…Doxycycline is used in the treatment of respiratory tract infection [5], lyme disease [6][7][8][9][10], psittacosis, relapsing fever, chancroid, cholera, campylobacter fetus infections, brucellosis, bubonic plague, Rocky mountain spotted fever and ehrlichiosis while being used for prophylaxis and treatment of leptospirosis [11] and Anthrax [12,13]. Some Grampositive bacteria have developed resistance to Doxycycline except Streptococcus pneumonia, Staphylococcus aureus and Bacillus anthracis while some infections caused by Gram-negative bacteria can be treated by Doxycycline such as Shigella species infections, Enterobacter aerogenes infections, Escherichia coli, Actinobacter species infections, Haemophilus influenza infections and Klebsiella species infections [14,15].…”
Section: Introductionmentioning
confidence: 99%